(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
The article examines the influence of blended feedstock on the parameters of the catalytic cracking process. The chemical composition of feedstock significantly affects the yield and quality of catalytic cracking products obtained. Therefore, there is an urgent need for extensive research that can significantly expand the range of feedstock by using heavy oil residues, such as fuel oil, by mixing them with traditional catalytic cracking feedstock. However, with the heaviness of the feedstock, the content of sulfur-containing, nitrogen-containing and oxygen-organic compounds, resins, metals and other substances that worsen catalytic cracking indicators increases. In this regard, feedstock preparation is one of the main issues in intensifying the catalytic cracking process. In order to intensify the catalytic cracking process, we prepared a feedstock mixture consisting of 70% by mass of straight-run fuel oil and 30% non-hydrotreated vacuum gas oil obtained by vacuum distillation of fuel oil from oil mixtures from the Buzachi, Aktyubinsk and Kumkol deposits. During the conducted studies, it was established that the introduction of up to 30% vacuum gas oil into the fuel oil composition contributes to a reduction in coke formation on the catalyst and an increase in the yield of the target product - gasoline, as well as a reduction in the amount of harmful emissions into the environment.